2017
DOI: 10.1111/head.13137
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Individual Headache Attacks Using Perceived Stress: Development of a Multivariable Prediction Model for Persons With Episodic Migraine

Abstract: Objective To develop and validate a prediction model that forecasts future migraine attacks for an individual headache sufferer. Background Many headache patients and physicians believe that precipitants of headache can be identified and avoided or managed to reduce the frequency of headache attacks. Of the numerous candidate triggers, perceived stress has received considerable attention for its association with the onset of headache in episodic and chronic headache sufferers. However, no evidence is availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 27 publications
5
90
2
Order By: Relevance
“…52 Multiple high-quality diary studies have demonstrated relationships between changes in stress and migraine attack onset [53][54][55][56] though the effect varies both inter-and intra-individually, and may interact with other trigger factors. 52 Multiple high-quality diary studies have demonstrated relationships between changes in stress and migraine attack onset [53][54][55][56] though the effect varies both inter-and intra-individually, and may interact with other trigger factors.…”
Section: Discussionmentioning
confidence: 99%
“…52 Multiple high-quality diary studies have demonstrated relationships between changes in stress and migraine attack onset [53][54][55][56] though the effect varies both inter-and intra-individually, and may interact with other trigger factors. 52 Multiple high-quality diary studies have demonstrated relationships between changes in stress and migraine attack onset [53][54][55][56] though the effect varies both inter-and intra-individually, and may interact with other trigger factors.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of the influence of trigger surprise on initiating new headache attacks is a secondary analysis of twice‐daily headache diaries collected as part of the Headache Prediction Study (HAPRED). The primary analysis of the study was fully reported previously . HAPRED was a prospective cohort study conducted between 2009 and 2014 in Winston‐Salem, NC.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Lipton et al [28] found no direct association between self-reported daily stress and migraine occurrence but instead found a significant association between stress recovery ("let down") and migraine onset over the following 6-24 h. Similarly, Houle et al [29] developed a predictive model for migraine in which average daily stress was used to forecast migraine attacks over the course of several days. In the short-term, migraine onset appears several hours to days after episodes of stress, which often leads migraineurs to identify stress as the main trigger for their headache symptoms [30].…”
Section: Discussionmentioning
confidence: 99%